Sweto Valley Enterprise / Anna Alicia Agustine... [et al.] - Okin, Beatrice; Paulus, Chriscella; Donis, Erziana; Jopulus, Roydee; Agustine, Anna Alicia (2014)
Sweto Valley Enterprise had select to open a cafeteria which produce food product based on sweet potatoes. Although this business is rarely exist especially in the area of Kata Kinabalu, we believed that this business that we are going to run have bright potential to be developed because this kind of cafeteria which served sweet potatoes-based food product had not been implemented in wider range of business. Other than that, our food products have various benefits in terms of health. Our food product is the perfect choice to be consumed especially for those who aim for a healthy and balanced diet. This is because sweet potatoes contain Vitamin B6 helps to reduce the chemical homocysteine in our bodies. Homocysteine has been linked with degenerative diseases, including the prevention of heart attacks. Other than that, it also contain vitamin C which is important to help ward off cold and flu viruses, few people are aware that this crucial vitamin plays an important role in bone and tooth formation, digestion, and blood cell formation. It helps accelerate wound healing, produces collagen which helps maintain skin's youthful elasticity, and is essential to helping us cope with stress. It even appears to help protect our body against toxins that may be linked to cancer. They contain_Vitamin D which is critical for immune system and overall health at this time of year. Both a vitamin and a hormone, vitamin D is primarily made in our bodies as a result of getting adequate sunlight. You may have heard about seasonal affective disorder ( or SAD, as it is also called), which is linked to inadequate sunlight and therefore a vitamin D deficiency. Vitamin D plays an important role in our energy levels, moods, and helps to build healthy bones, heart, nerves, skin, and teeth, and it supports the thyroid gland. Most people are aware that we need the mineral iron to have adequate energy, but iron plays other important roles in our body, including red and white blood cell production, resistance to stress, proper immune functioning, and the metabolizing of protein, among other things. Last but not least, Sweet potatoes are a good source of magnesium, which is the relaxation and anti-stress mineral. Magnesium is necessary for healthy artery, blood, bone, heart, muscle, and nerve function.